Proceedings of the Protactinium Chemistry Symposium : Gatlinburg, Tennessee, April 25-26, 1963 : sessions 1-111. - Protactinium Chemistry Symposium (1963 : Gatlinburg, Tennessee); U.S. Atomic Energy Commission; United States. Department of Energy. Office of Scientific and Technical Information; Oak Ridge National Laboratory (Oak Ridge, Tennessee : United States Atomic Energy Commission, Technical Information Service Extension, 1964)
Eleven papers are presented on the chemistry of protactinium. Most of the emphasis is on solvent extraction and solution chemistry. Separate abstracts were prepared for ten of the papers; the remaining paper was previously abstracted in NSA. (D.L.C.).
"Issuance Date: February 1964."
Published through the Information Bridge: DOE Scientific and Technical Information.
Includes bibliographical references.
Mode of access: Internet.
Keywords: Protactinium -- Congresses; Chemical reactions -- Congresses